The investigation and peculiarities of calculation of transport machine elements made of austempered ductile iron - Leonavičius, Mindaugas; Krenevičius, Algimantas; Šukšta, Marijonas; Posa, Jukka (Transport, 2003)
In this article the statical and cyclical strength investigations of austempered ductile cast iron (ADI) are presented. ADI material becomes more and more popular. Ductile iron is lighter than steel and its mechanical properties are better. ADI has good resistance to fatigue, high tensile strength, toughness and ductility. The fatigue crack initiation generally occurs in the graphite matrix. In the work the kinetic fatigue diagrams, longevity distributions laws and the mathematical model of crack growth ratio are described. The blanks of material were cut from a tooth of gear. Structure of the material consists of bainite and spherical graphite. The mechanical properties of ADI were obtained with assessment of chemical composition. The detennined statical mechanical properties of two different ADI materials are presented. The compact specimen was produced in order to detennine a threshold stress intensity factor. According to the investigations the stress intensity factor (threshold) is ΔK th = 9,8 MPa√m for the ADI 6.2.02 and ΔK th = 8,6 MPa√m for the ADI 9.4.02. The carried out investigations are insufficient for the complete evaluation of austempered ductile iron for the production of transport equipment elements. First Published Online: 19 Dec 2011